Arroz paddy: Preservación y tratamiento de granos almacenados - García Cevallos, Ana Belén (2020)
This paper was about paddy rice: preservation and treatment of stored grains. The Ecuadorian coast is the region where rice is grown, therefore it is necessary to know the preservation and treatment of stored paddy rice grains, to avoid damage to the seed, which will influence so that it does not lose its commercial value and quality. at the time of being piled and causing economic losses to farmers. Among the conclusions raised, it was determined that steel is a better material than concrete or wood to preserve the grain. Sheet steel silos are the ideal places to store grain, although since an important part is stored in bulk, one consideration to facilitate product aeration and inspection is to deposit it on plastic supports; On the other hand, a good preventive method to hinder the attack of insects in post-harvest is to avoid that the harvester produces physical damages in the paddy rice that make it more susceptible to damage by pests; the storage conditions did not affect the germination capacity of the paddy rice grain, which remained viable throughout the period, and the humidity and temperature conditions of the grain did not promote fungal development or the presence of mycotoxins; insects generally appear in the last months of storage, which is associated with an increase in grain temperature, therefore the storage conditions did not affect the health of the paddy rice grain from a fungal point of view, mycotoxin content and insects; study commercial storage of paddy rice, in fique packages previously treated with Deltamethrin, jointly avoiding the joint storage of several cereals in the same warehouse and use in the warehouse, for the control of stored grains insects, treatments with Deltamethrin, to provide greater protection and residuality, at a lower cost.